ANALISA DAYA SAING INDUSTRI PARIWISATA HALAL DI LOMBOK NUSA TENGGARA BARAT TAHUN 2019 - Putra, Fauzi Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
The background of this research is the phenomenon of halal tourism that continues to increase andbecome a trend in the development of the global economy, and Lombok as a region that has strongpotential and prospects in the development of halal tourism because it is known as an area that isclosely related to Islamic nuance. Therefore, this research discusses about the analysis of thecompetitiveness of the halal tourism industry in Lombok, West Nusa Tenggara. The purpose of thisresearch is to know the competitiveness analysis and SWOT analysis of the halal tourism industryin Lombok, West Nusa Tenggara. The research method in this study is qualitative descriptive usingthe triangulation model. This research uses the criteria or indicators set out in the Indonesia MuslimTravel Index report as a reference in determining the competitiveness of halal tourism in Lombok.Based on the results of the study concluded that the Indonesia Muslim Travel Index has set 4indicators for the development of halal tourism which includes Access, Communication,Environment and Services. In the development of halal tourism, Lombok has advantages inCommunication and Environment indicators and has weaknesses in Access and Services indicators.Keywords: Competitiveness, Halal Tourism Iindustry, Lombok, West Nusa Tenggara